2012
DOI: 10.1007/s13197-012-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Dahi containing Lactobacillus acidophilus and Bifidobacterium bifidum improves phagocytic potential of macrophages in aged mice

Abstract: The present study investigated the effect of Dahi containing potential probiotic bacterial strains on macrophage functions in ageing mice. Probiotic Dahi was prepared by co-culturing Dahi bacteria (Lactococcus lactis ssp. cremoris and Lactococcus lactis ssp. lactis biovar diacetylactis) along with Lactobacillus acidophilus LaVK2 (La-Dahi) or combined L. acidophilus LaVK2 and Bifidobacterium bifidum BbVK3 (LaBb-Dahi) in buffalo milk. The effect of ageing on phagocytic function was evaluated on 4 mo, 12 mo and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…Several studies have demonstrated that probiotics are able to reduce age-associated changes on phagocytic cells. It was reported that administration of the probiotic strains L. acidophilus LaVK2 or B. bifidum BbVK3 ameliorate age induced deficits in phagocytic activity of peritoneal macrophages with corresponding increase in production of reactive oxygen species [11]. It was also reported that oral administration of L. lactis subsp.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have demonstrated that probiotics are able to reduce age-associated changes on phagocytic cells. It was reported that administration of the probiotic strains L. acidophilus LaVK2 or B. bifidum BbVK3 ameliorate age induced deficits in phagocytic activity of peritoneal macrophages with corresponding increase in production of reactive oxygen species [11]. It was also reported that oral administration of L. lactis subsp.…”
Section: Resultsmentioning
confidence: 97%
“…Probiotic candidates have been accessed from very diverse habitats including faeces of breastfed human infants [65,69,80,85,95], faeces of healthy adults [9,15,65,70], faeces of elderly [81], faeces of children [25,96], breast milk [42], human saliva [52], vaginal isolates of healthy women [66,75], various fermented foods or beverages including raw or fermented milk [23,35,44], kefir [97], cheese [51,56,98], whey [99], yogurt [16,41], dahi [100,101], other dairy products [25,36,61], sourdough [102], sausages [17], fermented meat [24], kimchi [10,62], maize [25,59], fermented olives [103], Yerba mate [79], ragi [64], soy sauce [86], soil [104], as well as animal origin including rat faeces [71], geese [68], c...…”
Section: Discussionmentioning
confidence: 99%
“…У наш час у різних країнах світу L. acidophilus вводять у молочну сировину як монокультуру, так і у комплексі з різноманітними видами молочнокислих бактерій для виробництва кисломолочних продуктів (Kaushal and Kansal, 2014). Доведено можливість і доцільність спільного культивування мезофільних молочнокислих лактококів і ацидофільної палички (Dianawati et al, 2013), що дозволяє одержати у продукті досить високу концентрацію життєздатних клітин обох груп мікроорганізмів.…”
Section: вступunclassified